On The Uniqueness of Meromorphic Functions Sharing Three-Point Sets IM - Takahiro Kongo; Manabu Shirosaki (IndoMS, 2020)
We show that if two meromorphic functions on the complex plane shring some three-point sets IM, then they are identical under some conditions.